The Vasoreparative Potential of Endothelial Colony Forming Cells: A Journey Through Pre-clinical Studies - O'Neill, Christina L.; McLoughlin, Kiran J.; Chambers, Sarah E. J.; Guduric-Fuchs, Jasenka; Stitt, Alan W.; Medina, Reinhold J. (Frontiers in Medicine, 2018)
For over a decade various cell populations have been investigated for their vasoreparative potential. Cells with the capacity to promote blood vessel regeneration are commonly known as endothelial progenitor cells (EPCs); although such a definition is currently considered too simple for the complexity of cell populations involved in the reparative angiogenic process. A subset of EPCs called endothelial colony forming cells (ECFCs) have emerged as a suitable candidate for cytotherapy, primarily due to their clonogenic progenitor characteristics, unequivocal endothelial phenotype, and inherent ability to promote vasculogenesis. ECFCs can be readily isolated from human peripheral and cord blood, expanded ex vivo and used to revascularise ischaemic tissues. These cells have demonstrated efficacy in several in vivo preclinical models such as the ischaemic heart, retina, brain, limb, lung and kidney. This review will summarise the current pre-clinical evidence for ECFC cytotherapy and discuss their potential for clinical application.